Biomechanics associated with tibial stress fracture in runners: A systematic review and meta-analysis - Milner, C. E.; Foch, E.; Gonzales, J. M.; Petersen, D. (Journal of Sport and Health Science, 2023)
Background Tibial stress fracture (TSF) is an overuse running injury with a long recovery period. While many running studies refer to biomechanical risk factors for TSF, only a few have compared biomechanics in runners with TSF to controls. The aim of this systematic review and meta-analysis was to evaluate biomechanics in runners with TSF compared to controls.